Optimization of pressurised intermittent microwave assisted extraction of pectin from Thai soybean hulls - Lamnambhorn Sobmor; K Banjong (My University, 2020)
Soybean (Glycine max), a major crop worldwide, is used to produce oil for cooking and for industrial purposes such as production of soy milk, soy sauce and biodiesel fuel. The hulls are mainly used as animal feed but they can be used for pectin extraction for food industries; but, the methods currently used for extraction have limited efficiency. Therefore, pressurised intermittent microwave-assisted extraction (PIMAE) was tested to extract pectin from soybean hulls from either flakes (SHF) or flakes ground into powder (SHP). Pressurised intermittent microwave-assisted extraction reduced both extraction time and solvent consumption. It also uses a by-product of a processed crop and is an environmentally friendly technology. Box-Behnken response surface design was utilized to study and optimize the effects of processing variables, which included pH from 1.5 to 2.5, pulse ratios from 1.0 to 1.51 and extraction time from 5 to 15 min on pectin yield. The degree of esterification of pectin was measured since it affects pectin’s commercial value as a gelling and thickening agent. The amount of pectin extracted increased with increasing extraction time and reduced as the pH and pulse ratio increased. The conditions that resulted in the highest pectin yield were pH 2 pulse ratio 1.0 and extraction time 15 min, which gave 6.42% from SHF samples and pH 1.5, pulse ratio 1.0 and extraction time 10 min, which gave 12.09% from SHP samples. The conditions that produced the highest percentage of esterification were pH 2.5, pulse ratio 1.25 and extraction time of 5 min, which gave 80.81% for SHF and 80.59% for SHP samples. The extracted pectin contained high levels of methoxy pectin. Levels of pectin yield and degree of esterification were below the predicted theoretical values from the Box-Behnken response surface design, despite the good fit of the models, which were 0.99 R2 for SHF and 0.98 R2 for SHP for yields of pectin and 0.97 R2 for SHF and 0.98 R2 for SHP for the degree of esterification of pectin. In these optimal conditions, experimental yield correlated with predicted yields.
Keywords: Pectin; Polysaccharides and Plant Cell Walls